Correlation of serum vitamin D with hip fracturesin males more than 50 years of age - Hari Krishna Mata; Dinesh Chand Gupta; Nataraj A.R (International Journal of Medical Research and Review, 2015)
Introduction: Vitamin D is vital for bone health because it assists in the absorption and utilization of calcium. There are various studies in elderly females with hip fractures correlating the Vitamin D levels. But very few studies have evaluated the serum Vitamin D levels in males more than 50 years.Materials and Methods: Present study was conducted in the JIPMER Pondicherry between August 2012 and August 2013. A total of 41 male patients aged more than 50 years with fracture neck of femur and Intertrochanteric fracture were included. Blood samples were taken stored, processed and evaluated for vitamin D total (D2 and D3). The Values of Vitamin D obtained are shown into three groups as 0-20ng/ml-deficiency, 20-30ng/ml as insufficiency and>30ng/ml as normal Reference.Results: On analysis of Vitamin D we found that out oftotal 41 patients 9(22%) had vitamin D level <20ng /ml, 15(36%) had levels between 20ng-30ng/ml and 17 (41%) had >30ng/ml. Of the 21 patients with Neck of femur fractures Vitamin D<20ng/ml are 6(28.6%), 20-30ng/ml are 9 (42.9) and >30ng/ml are 6(35.3).Vitamin D levels in 20 intertrochanteric fractures are<20ng/ml in 3(15%), 20-30ng/ml in 6(35%) and >30ng/ml in 11(55%).Conclusion: We found 24 patients (58%) have vitamin D level <30ng/ml, more in patients with neck femur fracture than intertrochanteric fractures. Present study found that there is no statistically significant correlation between the vitamin D level and proximal femoral fractures in elderly males (p=0.489).